Postglacial phylogeography, admixture, and evolution of red spruce (Picea rubens Sarg.) in Eastern North America - Bashalkhanov, Stanislav; Johnson, Jeremy S.; Rajora, Om P. (Frontiers in Plant Science, 2023)
Climate change is a major evolutionary force that can affect the structure of forest ecosystems worldwide. Red spruce (Picea rubens Sarg.) has recently faced a considerable decline in the Southern Appalachians due to rapid environmental change, which includes historical land use, and atmospheric pollution. In the northern part of its range, red spruce is sympatric with closely related black spruce (Picea mariana (Mill.) B.S.P.), where introgressive hybridization commonly occurs. We investigated range-wide population genetic diversity and structure and inferred postglacial migration patterns and evolution of red spruce using nuclear microsatellites. Moderate genetic diversity and differentiation were observed in red spruce. Genetic distance, maximum likelihood and Bayesian analyses identified two distinct population clusters: southern glacial populations, and the evolutionarily younger northern populations. Approximate Bayesian computation suggests that patterns of admixture are the result of divergence of red spruce and black spruce from a common ancestor and then introgressive hybridization during post-glacial migration. Genetic diversity, effective population size (Ne) and genetic differentiation were higher in the northern than in the southern populations. Our results along with previously available fossil data suggest that Picea rubens and Picea mariana occupied separate southern refugia during the last glaciation. After initial expansion in the early Holocene, these two species faced a period of recession and formed a secondary coastal refugium, where introgressive hybridization occurred, and then both species migrated northward. As a result, various levels of black spruce alleles are present in the sympatric red spruce populations. Allopatric populations of P. rubens and P. mariana have many species-specific alleles and much fewer alleles from common ancestry. The pure southern red spruce populations may become critically endangered under projected climate change conditions as their ecological niche may disappear.